Climate Change Awareness on Pakistani Electronic Media: A Literature Survey - Shah, Syed Zulqarnain; Shahid, Muhammad; Mahmood, Farrah (Regional Lens, 2025)
The electronic media constitutes a source of awareness creation and transmission about climate change in Pakistan, which is discussed in this literature review based on the results of 25 research papers that are available in the national, regional, and international levels. The results reveal that the coverage of climate in Pakistan is generally shallow and often of disaster nature in character, which attracts the attention of the media during such events and is even more infrequently heard; the experts speaking on this issue. Another point in the literature was also the fact that framing of climate stories can be influenced by political interests, restrictions in the newsrooms and pressures in the background by commercial circles. Besides that, there is no local and relevant reporting in mainstreams by the community that fosters lack of interest in audiences and lack of understanding of climate science in all people. The authoritative reports on audience-oriented studies state that the mere exposure to media does not lead to change in behavior or information when the coverage is shallow and hard to act upon. All in all, the survey ends with the statement that although Pakistani electronic media can potentially play an important part in the context of increasing awareness of climate change, the opportunity is limited by structural and professional constraints. To enhance climatic communication and aid awareness in Pakistan, it is necessary to strengthen environmental journalism, introduce the element of scientific capability, and encourage solution-based reporting.